Comparison of growth performance and rumen metabolic pathways in sheep and goats under the same feeding pattern - Lin, Xueyan; Ju, Lin; Cheng, Qianjin; Jiang, Yue; Hou, Qiuling; Hu, Zhiyong; Wang, Yun; Wang, Zhonghua (Frontiers in Veterinary Science, 2023)
Diet and species are important factors affecting the rumen microbiota, with roughage stimulating rumen development and concentrate feeds being broken down by the decomposition of Ruminal flora to provide the organism with a large amount of energy. This study aimed to explore the effects of host and dietary factors on rumen flora composition and diversity, as well as on host metabolism. The study reports the research conducted on 5-month-old male Small-tail Han sheep and 5-month-old male Boer goat, each with an average weight of 33.87 ± 1.70 kg. Five animals of each species were divided into two groups, namely, the S group (Small-tail Han sheep) and the B group (Boer goat). The experiment was carried out in two various periods, namely, X and Y for groups S and B, respectively. The rations were fed with concentrate-to-roughage ratios of 3:7 and 5:5, respectively. Growth performance was measured by the weight increase index. The results showed that, under the same raising conditions, the ratio between body weight increases and the amount of feed was lower in the S group than in the B group, but the differences were not significant. According to the analysis of the apparent digestibility ratio of nutrition ingredients, the XS group had a significantly higher apparent digestibility ratio for acid detergent fiber than the XB group (p < 0.05). Even though the analysis of rumen fermentation parameters showed that the rumen pH has no significant differences between the XS and XB groups, it was significantly lower in the YS group than in the YB group. The XS group contained a significantly lower content of total volatile fatty acids than the XB group (p < 0.05). Analysis of the 16S rDNA sequencing results revealed that, compared to the B group, the S group was highly enriched with the following bacteria: Proteobacteria, γ-proteobacteria, Aeromonadales, and Succinivibrionaceae. Thus, the host species affected the abundance and diversity of rumen bacteria. Feed utilization efficiency of Small-tail Han sheep was higher than Boer goats, which might be specifically associated with Succinivibrionaceae. The results from this study show that animals belonging to the same family but different genera and species can differ in metabolic pathways even when they are provided with the same animal feed.